EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK DENGAN METODE TALKING STICK BERBANTUAN MODUL SISWA KELAS III SD KANISIUS KURMOSARI SEMARANG - Aldrova Nadeak; Andarweni Astuti; Yustinus Joko Wahyu Yuniarto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2022)
The problem in this study is that the learning that is commonly used in class III SD Kanisius Kurmosari Semarang is conventional teacher-centered learning so that students only listen and accept what is given by the teacher, so that the responsibility of students to participate in learning is still low. The purpose of this study was to determine the learning responsibilities of third grade students at SD Kanisius Kurmosari Semarang had a positive effect on religious learning outcomes, to determine the difference in responsibilities between the Talking Stick with module assistance and conventional learning for third grade students at SD Kanisius Kurmosari Semarang, to find out the average the average grade III religious learning outcomes at SD Kanisius Kurmosari Semarang by using the Talking Stick learning conventional. The method used in this research is a quantitative approach research method. Data collection techniques using observation sheets, tests and documentation. The results of this study indicate that the effect of responsibility on learning outcomes obtained from R square is 89.2%. The difference in the average score of responsibility in the experimental class is 3.38 and the control class is 2.81. The difference in the average value in the experimental class is 82.96 and the control class is 66.51. With the results of the N gain score using the Talking Stick is quite effective in learning is 77.9% while using conventional less effective is 42.8%.